SISTEM INFORMASI PERPUSTAKAAN HIBRIDA - Nur Hakim, Fitro; Anang Wijayanto, Suitbertus (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2021)
Hybrid library is a library that combines the traditional library and digital library. Hybrid library services include a library automation and digital library services. Library services with the conventional method still raises a lot of obstacles to perpustaakaan members such as the length of time the service and lack of interest in library members to visit the school library. The use of cellular technology used by the public and the prices are getting cheaper mobile phone operations, making cellular technologies such as SMS into one option to improve services and reduce the constraints faced by the library. SMS as an increase in the utilization of library services possible to apply in the library. SMS Gateway technology become one answer to the utilization of mobile technology in the library. Another obstacle faced by the school library is a limited number of physical libraries than the number of students who are relatively more. Support the development of school libraries is less than support for other aspects of school development. A limited number of books that can be solved by implementing the use of digital book or ebook, and audio libraries to increase library holdings.